Power grid fault detection and diagnosis method - ZHAO HUIJUAN; XU CHAOFENG; WU JINGWEI; ZHAO YONG; HU CHANGSHI (2015)
A power grid fault detection and diagnosis method of the invention comprises the following steps: presetting line fault judgment parameters; acquiring the current at the primary side of a transmission line, and rectifying the current; sampling the rectified alternating current and zero-sequence current at a predetermined time interval, and analyzing the sampling result to judge whether or not to start a timer; using fault wave recorders installed inside a substation to record fault data of a primary system of a power grid at certain sampling frequency, and completing mapping from wave recording and sampling to equipment current recording; realizing sampling synchronization of wave recording data of different fault wave recorders according to the absolute moment of sampling; and measuring and analyzing the differential current of the primary current of the power grid, and comparing the differential current value with a set differential current value to locate the fault position and determine the protection action. By adopting the power grid fault detection and diagnosis method of the invention, the accuracy of line fault indication of a fault indicator is improved, the rate of false alarm is reduced, and line fault and line real-time operation state can be better monitored.